Stable isotope analysis of human bone and ethnohistoric subsistence patterns in Tierra del Fuego - Yesner, David (2003)
Ethnohistoric records from Tierra del Fuego suggest that precontact Fuegians could be subdivided into three major groups: the Yamana, maritime hunter-gatherers of the Beagle Channel and islands to the south; the Selk’nam, terrestrial hunter-gatherers of southernmost Patagonia; and the Haush, a little-known group that seems to have combined elements of both Yamana and Selk’nam lifeways. However, the observed ethnographic patterns reflect societies whose way of life was significantly altered by European contact, habitat alteration, and exploitation of some of the key resources upon which Fuegian peoples were historically dependent. To test the linkage between ethnohistorically recorded subsistence patterns and prehistoric lifeways in the region, stable carbon and nitrogen isotopes were assayed from human burials that date within the last 1500 years before European contact. Isotopic analyses substantially confirm the ethnohistorically documented patterns, but also reveal some anomalies, such as Yamana populations who may have been more dependent on terrestrial resources (i.e., guanaco). Data from the Haush region suggest primary dependence on marine resources, like the Yamana, while the Selk’nam demonstrate limited use of such resources. Stable isotopic analysis can thus be used to test hypotheses concerning the validity of archaeological and ethnohistoric data.